Surveillance in inflammatory bowel disease: is chromoendoscopy the only way to go? A systematic review and meta-analysis of randomized clinical trials - Resende, Ricardo Hannum; Ribeiro, Igor Braga; de Moura, Diogo Turiani Hourneaux; Galetti, Facundo; Rocha, Rodrigo Silva de Paula; Bernardo, Wanderley Marques; Sakai, Paulo; de Moura, Eduardo Guimarães Hourneaux (Endoscopy International Open, 2020)
Background and study aims Ulcerative colitis (UC) and Crohn’s disease (CD) have higher risk of colorectal cancer (CRC). Guidelines recommend dysplasia surveillance with dye-spraying chromoendoscopy (DCE). The aim of this systematic review and meta-analysis was to review all randomized clinical trials (RCTs) available and compare the efficacy of different endoscopic methods of surveillance for dysplasia in patients with UC and CD.Methods Databases searched were Medline, EMBASE, Cochrane and SCIELO/LILACS. It was estimated the risk difference (RD) for dichotomous outcomes (number of patients diagnosed with one or more dysplastic lesions, total number of dysplastic lesions diagnosed and number of dysplastic lesions detected by targeted biopsies) and mean difference for continuous outcomes (procedure time).Results This study included 17 RCTs totaling 2,457 patients. There was superiority of DCE when compared to standard-definiton white light endoscopy (SD-WLE). When compared with high-definition (HD) WLE, no difference was observed in all outcomes (number of patients with dysplasia (RD 0.06; 95 % CI [–0.01, 0.13])). Comparing other techniques, no difference was observed between DCE and virtual chromoendoscopy (VCE – including narrow-band imaging [NBI], i-SCAN and flexible spectral imaging color enhancement), in all outcomes except procedure time (mean difference, 6.33 min; 95 % CI, 1.29, 11.33). DCE required a significantly longer procedure time compared with WLE (mean difference, 7.81 min; 95 % CI, 2.76, 12.86).Conclusions We found that dye-spraying chromoendoscopy detected more patients and dysplastic lesions than SD-WLE. Although no difference was observed between DCE and HD-WLE or narrow-band imaging, the main outcomes favored numerically dye-spraying chromoendoscopy, except procedure time. Regarding i-SCAN, FICE and auto-fluorescence imaging, there is still not enough evidence to support or not their recommendation.